Effect of partial soil wetting on transpiration, vegetative growth and root system of young orange trees (Scientia Agricola, 2015)
The wetted area fraction is a factor critical to the success of drip irrigation. This study aimed to evaluate the effect of partial soil wetting on transpiration, vegetative growth and root system of young orange trees. The experiment was carried out in a greenhouse where plants were grown in 0.5 m3boxes internally divided into compartments. The wetting of 12 % of soil area was tested on two types of soil cultivated with ‘Valencia’ orange trees grafted onto Rangpur lime and ‘Swingle’ citrumelo rootstocks. Transpiration was determined in 40 plants. Water extraction and root density were evaluated in the compartments. Transpiration is reduced by restriction in wetted soil area, and such reduction is influenced by the number of days after the beginning of partial irrigation, atmospheric evaporative demand and plant phenological stage. Mean transpiration of plants with partial irrigation was equivalent to 84 % of the mean transpiration of plants with 100 % of wetted soil area in the period studied. However, after 156 days of imposing partial irrigation there was no difference in transpiration between treatments. Plant acclimation was caused by an increase in root concentration in the irrigated area. After a period of acclimation, if the entire root system is wetted, soil water extraction becomes proportional to the percentage of wetted area after a short period of time. Despite the reduction in transpiration, there was no difference between treatments with 12 % and 100 % of wetted soil area in terms of vegetative growth.